Nanoconfinement degradation in NaAlH4/CMK-1 - Chumphongphan, Somwan; Filso, U.; Paskevicius, Mark; Sheppard, Drew; Jensen, T.; Buckley, Craig (Elsevier Ltd, 2014)
An ordered mesoporous carbon scaffold (CMK-1) has been synthesized and infiltrated with NaAlH4 nanoparticles by solvent- and melt-infiltration techniques. Small angle X-ray scattering (SAXS), powder X-ray diffraction (XRD), scanning electron microscopy (SEM), Transmission Electron Microscopy (TEM) and energy dispersive spectroscopy (EDS) are used to characterize the structure, composition and morphology before and after thermal treatment. This study illuminates some of the problems that can be associated with nanoconfinement of hydrogen storage materials including scaffold contamination, residual solvent contamination, sample morphology changes after heating, and other factors that can be detrimental to the application of these systems. Of particular interest is the expulsion of NaAlH4 decomposition products from the scaffold after heating beyond its melting point under vacuum. This results in the surface of mesoporous carbon particles having arrays of multi-micron-long Al filaments that are >100 nm in diameter.